Boswellic acid sensitizes gastric cancer cells to Cisplatin-induced apoptosis via p53-mediated pathway - Shadia Al-Bahlani; Ikram A. Burney; Buthaina Al-Dhahli; Safiya Al-Kharusi; Fakhra Al-Kharousi; Amani Al-Kalbani; Ikhlas Ahmed (BMC, 2020)
Abstract Background Cisplatin (CDDP) is an effective anticancer drug for Gastric cancer (GC) that induces apoptosis by altering pro- (p53) and anti-apoptotic (Akt and NFkB) proteins; however, chemoresistance remains a big challenge. Additional compounds with promising anticancer effects such as AKBA (Acetyl-keto-beta boswellic acid) may overcome the resistance. However, its role in CDDP-induced apoptosis in GC has not been studied. This study aimed to examine the effectiveness of AKBA on p53-mediated, CDDP-induced apoptosis in GC cells. AGS and NCI-N87 cells were treated with different concentrations (0, 25, 50, 100 μM) of CDDP and/or AKBA. Methods P53, Akt and NFkB proteins and apoptosis were assessed by Western blot and flow cytometry. The role of p53 was determined by inhibiting its function via the siRNA approach. Results The results revealed that CDDP and AKBA significantly increased p53 content in both cells, while Akt and NFkB were significantly decreased. Both compounds significantly induced apoptosis in a dose-dependent manner. AKBA sensitized GC cells to CDDP-induced apoptosis by altering the protein expression. P53 downregulation affected Akt and NFkB proteins with a slight increase in apoptosis induction in the combination treated groups. Conclusions Altogether, our findings suggest that AKBA enhances GC cell sensitivity to CDDP-induced apoptosis via the p53 pathway.